'Long COVID': Symptom persistence in children hospitalised for COVID‐19. (19th July 2022) - Asadi‐Pooya, Ali A; Nemati, Meshkat; Nemati, Hamid
Abstract : Aim: We aimed to describe the long‐term outcome with respect to symptom persistence amongst children hospitalised for COVID‐19. Methods: This was a follow‐up study of 58 children and adolescents hospitalised with COVID‐19. For all patients, the data were collected in a phone call to the family in December 2021 (9 months after the initial study and more than 13 months after their admission to hospital). We inquired about their current health status and obtained information, if the responding parent consented orally to participate and answer the questions. Results: Fifty‐one children and adolescents were studied. Only five patients (10%) had persistent symptoms compatible with long‐COVID; the reported symptoms include fatigue in four (8%), weakness in three (6%), exercise intolerance in two (4%) and shortness of breath in two (4%) patients. Four patients (7.8%), who did not have any symptoms of long‐COVID in phase 1 of the study, reported new‐onset symptoms or complaints that are potentially compatible with the diagnosis of long‐COVID (weakness, myalgia, excess sputum, cough, fatigue) in the current phase. Conclusions: Symptom persistence of long‐COVID is infrequent amongst children hospitalised for COVID‐19. Most of the symptoms of long‐COVID will resolve with the passage of time and the residual symptoms are often mild and tolerable. The scientific community should carefully and clearly define long‐COVID and its natural course in order to facilitate and harmonise future studies.